Cultural geography of folk houses - Pawar, R. S., 1948- (Jaipur, India : Pointer Publishers, 1992)
Study of the Lower Chambal region.
Includes index.
Includes bibliographical references (p. [196]-209).
Keywords: Dwellings -- India -- Chambral River Region; Vernacular architecture -- India -- Chambral River Region; Human geography -- India -- Chambral River Region; Chambral River Region (India) -- Social life and customs